Optical properties of ordered ZnO/Ag thin films on polystyrene spheres. Issue 15 (22nd August 2017) - Li, Xiu; Chen, Xiuyan; Xin, Zhiqing; Li, Luhai; Xu, Yanfang
Abstract: A thorough research of the optical properties of ZnO/Ag structures sputtered by RF on PS colloidal crystal molds with different diameters is reported. The influences of the period of the substrates on the performance of ZnO thin films were studied. The results of scanning electron microscopic, X-ray diffraction patterns and UV–vis absorption spectroscopy indicated that the ZnO/Ag thin films were well-covering on PS colloidal crystal molds. The diameter of the polystyrene particles significantly influenced the PL spectrum intensity of ZnO/Ag by affecting the interferences of light. After adding PS colloidal crystal molds with different diameters, all the samples show two luminescent regions, namely a strong, narrow UV emission peak and a wide, weak visible emission band. However, the signal of UV emission increases more significantly. In particular, the maximum enhancement occurs when the diameter is 300 nm. This work proposes an effective way to improve ZnO light emission based on a simple, rapid and cost effective method to fabricate ordered periodic substrates by preparing single layer polystyrene microspheres masks.